Breeding Performances of the European Blackbird (Turdus merula) in Morocco: Habitat Selection, Breeding Phenology, and Breeding Success - Abderahim El Hassani; Ismail Mansouri; Wafae Squalli; Abdelbari El Agy; Amine Assouguem; Kenza Bouayad; Abdellah Markou; Mohamed Mounir; Hamid Achiban; Mohamed Dakki; Lahsen El Ghadraoui (International Journal of Zoology)
The European Blackbird (Turdus merula) is a widespread species. In Morocco, available knowledge on this species is limited to a few descriptive pieces of information with no detailed data provided. With climate change and the intensification of agricultural activities, the study of the breeding performances of this species is indispensable for management purposes. This study investigates breeding biology, nesting habitats, breeding chronology, and reproductive success of the European Blackbird in both apple orchards and surrounding woody vegetation at Ait Ayach (Morocco) between March and August 2016. We monitored weekly nest status, nesting sites, breeding dates, and failure factors. Results showed that the European Blackbird nests mainly in apple orchards, on Golden Delicious and Starkrimson Delicious trees. Nest height above the ground was 214.15 ± 0.09 cm. Blackbird nests were cup-shaped with medium size dimensions and built from twigs, including dry leaves, stems, and roots walled by the mud. Breeding activities started firstly by nest construction during the last week of April, secondly by egg laying during the first week of May, and thirdly by hatching during the second week of May. Among the 74 surveyed nests, 100% were active during the nesting phase and 88.38% of eggs have succeeded during the incubation phase. In total, 69.03% of chicks have been emancipated. In short, 15.9% of clutches were attacked by predators, 14.35% of clutches were failed due to nest desertion, and 8.75% of chicks were dead. Our study provides the first and only detailed data on reproductive parameters of the European Blackbird in Moroccan ecosystems. Data collected from this study provide valuable information for long-term monitoring of the Moroccan Blackbird population. Additionally, our data offer a possibility of large-scale comparative studies of the reproductive ecology of the Blackbird species.